NEETs, North South Divergence and Economic Security in the Euro Area in the Aftermath of the Crisis - Szymanowski, Rafał (Adam Mickiewicz University, 2019)
The euro was intended to bring more economic and political convergence between European countries. This was the main promise of the French Monetarists during the founding debate on European monetary integration, as well as European leaders who decided to permanently fix exchange rates and introduce the euro. Moving forward on the path towards “ever closer union” was the greatest hope of both the architects of the common currency and its political supporters. However, as a result of the eurozone crisis, European countries actually diverged from each other. The main argument of this paper is straightforward: the financial and banking crisis in the euro area gave rise to the dangerous divide between the core “surplus” countries in the north and peripheral “deficit” countries in the south. In this paper, I examine this divergence by looking at one crucial indicator: the number of young people who are unemployed and inactive (NEET) in the northern and southern countries of the eurozone, before and after the financial crisis.
Keywords: NEETs; not in employment education or training; Euro Area; Eurozone; Euro crisis; Eurozone crisis; European Union; Europe; economic security; Eurozone core; Eurozone periphery; Greece; single currency